Uniquecare takaful / Muhammad Sa'di Mohd Saman ... [et al.] - Mohd Saman, Muhammad Sa'di; Abdul Azis, Nur Aimi; Mohammad Hatta, Mohammad Firdaus; Hanif, Azlina (2021)
The Islamic finance industry has seen tremendous growth around the world, one of the markets is takaful market. Takaful is an alternative to conventional insurance because conventional insurance contains interest, uncertainty, and gambling that is forbidden in Islamic practice. Nowadays, takaful has implemented various products offered to public in order to strengthen its position in the industry and increase its market share over the conventional insurance industry. However, takaful plan focuses only on normal children. There is no takaful product that is offered to physically disabled children. Hence, this study aims to give some knowledge and awareness as well as creating new product development related to physically disabled children. This study has applied quantitative and qualitative methods in which about 50 questionnaires have been distributed to parents with disabled children through online survey because of Covid-19 pandemic. By using descriptive analysis, the results indicate that all respondents have knowledge, aware and will participate if any takaful product is offered to protect their physically disabled children. Therefore, the product to be created is named UniqueCare Takaful that provides financial protection to children with physical disabilities.